A Application of Joyful Learning Learning Model assisted by GPS Harta Karun to Increase Student Motivation in Thematic Learning at SD Negeri 2 Lamokato - Kasmawati Kasmawati (Amanah: Jurnal Amanah Pendidikan dan Pengajaran, 2020)
The purpose of this research is the application of the Joyful Learning Learning Model assisted by GPS Harta Karun to Increase Student Motivation in Thematic Learning in SD. The research was conducted on 5th-grade students of SDN 2 Lamokato Kab. Kolaka semester 1 of the 2018-2019 academic year, especially in thematic subjects. Grade 5 students who will be studied include a class where most of the students have low learning motivation. The number of students was 34 students. Primary data obtained from test scores and student motivation questionnaires. Secondary data were obtained from the results of observations made by collaborators using teacher and student activity observation sheets. The results showed that: (a) The joyful learning model assisted by the treasure trove of GPS could increase students' motivation to learn in thematic subjects in grade 5 SDN 2 Lamokato. The increase in student learning motivation by 70.6% in the first cycle to 79.4% in the second cycle; and (b) a joyful learning model that can increase student motivation in this study is joyful learning assisted by "GPS treasure" (Powerpoint spin game in cycle I and a treasure-seeking game).